Testing a Measurement Model of BIM Potential Benefits in Iraqi Construction Projects - Wadhah Amer Hatem; Abbas Mahde Abd; Nagham Nawwar Abbas (Salehan Institute of Higher Education, 2017)
Building Information Modeling (BIM) is an integrated and comprehensive system for all that related to the construction project, which includes a set of effective policies, procedures, and computer applications that increase the performance of the project during its life cycle. The objective of this research develops a clear concept about the BIM adoption in Iraq through investigating potential benefits that can be obtained through its application in construction projects also build a measurement model for these benefits. The research methodology was based on quantitative approach which adopted by conducting a questionnaire directed to professionals in the field of construction projects in the public and private sectors supported by personal interviews with respondents either individually or in groups. Three hundred copies of the forms were distributed to the companies, firms and engineering departments of the various ministries of the state. After the data was obtained, two software (SPSS and SmartPLS) was used for analyzing the data and constructing the measurement model. The results showed of all the benefits constructed within three key components. The first is knowledge support for management in term of (costs, data, processes), the second is effective design performance and the third is effective construction performance and all these components were modeled as a measurement model.